Minority shareholder's remedies - Boyle, A. J. (Cambridge studies in corporate law., 2002)
The state of English company law on minority shareholders' remedies is analysed in the light of the UK Law Commission, further appraised by the Company Law Review Steering Group. As well as considering the complexities of derivative actions and statutory minority remedies, Boyle discusses future directions for minority shareholders' remedies.